ANALISIS EMISI GAS RUMAH KACA (GRK) DARI MESIN PEMBAKARAN DENGAN APLIKASI SANGEA DI PT. CHEVRON PACIFIC INDONESIA (STUDI KASUS PADA TURBIN GAS MINAS 10) - Maladi M. Mustar; Usman M Tang; Nofrizal ' Nofrizal (Jurnal Ilmu Lingkungan, 2014)
This study analyzes the greenhouse gas estimation calculation for CO 2 and NO x (asNO 2 ) emissions. Estimation is calculated using the SANGEA application which is basedon the fuel gas consumption and composition for the combustion engine. The estimationcalculations are then compared with the results of on a direct measurement by using acontinuous emission monitoring system (CEMS.) Furthermore, the estimationcalculation is referred to some related regulations to see if it meets with the standard, toknow the quality levels or “tier” and reliability of the SANGEA application used, alsoto learn more on the strategy undertaken by emitters in managing GHG emissions. Thestudy methodology used is descriptive qualitative analysis by performing field survey tolearn how to perform direct measurements with continuous emission monitoringequipment or CEMS in place (in situ) and how to calculate estimation emissions usingthe SANGEA applications for the operation of combustion engines or turbines. Theresult of this study shows that there are differences result between the SANGEAcalculation and CEMS direct measurement, where the SANGEA calculation result is19.7 - 27.8% lower than the direct measurement and this difference result is still closewith the previous studies that have been done, 18.3 to 30.7%, which is becomes atheoretical reference for this comparison calculation and direct measurement study.